Mineral elements in sheep cheese - Hrković Porobija, Amina (Array, 2020)
The indigenous Travnik (Vlasic) cheese is produced in central Bosnia in the area of Mt. Vlasic. This cheese belongs to the group of white soft cheeses, ripened in brine under anaerobic conditions, and made from raw, thermally untreated sheep"s milk. The production technology is very simple and is adapted to mountainous conditions. Cheese is an important source of essential nutrients, in particular proteins, fat, vitamins and minerals. The aim of this study was to determine the concentration of macroelements (Ca, Na, K, Mg, P) and microelements (Zn, Fe, Cu) in 15 samples of Travnik sheep cheese using the atomic absorption spectrometry (AAS) and ultraviolet–visible spectrometry (UV-VIS) methods. A tendency of increasing Mg and K, Fe and Ca, Fe and Mg, and Fe and P was determined in the examined samples, but without statistical significance.